2008
DOI: 10.1080/15438620701877032
|View full text |Cite
|
Sign up to set email alerts
|

Exercises Following Anterior Cruciate Ligament Reconstructive Surgery: Biomechanical Considerations and Efficacy of Current Approaches

Abstract: To enable a safe, effective return to daily functional activities and to prevent premature knee joint osteoarthritis, adults undergoing anterior cruciate ligament (ACL) surgery require carefully designed and appropriate rehabilitation strategies. In this article we critically examine the contemporary body of literature concerning the application and outcomes of various knee exercise rehabilitation protocols described in the literature in the context of the surgically repaired ACL injured knee. These data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 60 publications
2
15
0
5
Order By: Relevance
“…Frost's mechanostat theory supports that the greatest mechanical loading of bone is predominately due to muscle forces [22,55]. However, after periods of extended bed rest [56] or space flight [57,58] [42,[59][60][61]. The present study demonstrated that when quadriceps muscle force remains uniform across models, the supine model produces more shear force than the standing model which is consistent with ACL literature.…”
Section: Chapter 5 Discussionsupporting
confidence: 82%
“…Frost's mechanostat theory supports that the greatest mechanical loading of bone is predominately due to muscle forces [22,55]. However, after periods of extended bed rest [56] or space flight [57,58] [42,[59][60][61]. The present study demonstrated that when quadriceps muscle force remains uniform across models, the supine model produces more shear force than the standing model which is consistent with ACL literature.…”
Section: Chapter 5 Discussionsupporting
confidence: 82%
“…Besides this advantage, CKC exercises may reduce patellofemoral pain, 5 enhance knee proprioception, 5 and may be more effective for restoring normal knee function, including muscle strength and joint range of motion. 13 Individuals who perform predominantly CKC exercises during their rehabilitation also tend to be more satisfied with the end result. 15 …”
Section: Discussionmentioning
confidence: 99%
“…105 In general, rehabilitation programs after ACL reconstruction in adults have moved in a more aggressive direction, including early weight bearing, more powerful strength training, challenging neuromuscular and plyometric exercises, and an earlier return to sport. 12, 31,42,102 In contrast, the sparse descriptions of rehabilitation programs for skeletally immature individuals appear to advocate a more conservative approach, with longer periods of non-weight bearing and bracing, and a later return to sport. 66,67,100 The slower and more conservative protocols for skeletally immature patients who undergo ACL reconstruction may be due to the uncertainty regarding the strength of the graft and the risk of growth disturbances, as well as the lack of evidence-based practice guidelines.…”
Section: Physeal Sparing Reconstructionmentioning
confidence: 99%